Therapeutic Potentials of Aconite-like Alkaloids: Bioinformatics and Experimental Approaches - Mares, Catalina; Udrea, Ana-Maria; Buiu, Catalin; Staicu, Angela; Avram, Speranta (Mini Reviews in Medicinal Chemistry, 2024)
Compounds from plants that are used in traditional medicine may have medicinal properties. It is well known that plants belonging to the genus Aconitum are highly poisonous. Utilizing substances derived from Aconitum sp. has been linked to negative effects. In addition to their toxicity, the natural substances derived from Aconitum species may have a range of biological effects on humans, such as analgesic, anti-inflammatory, and anti-cancer characteristics. Multiple in silico, in vitro, and in vivo studies have demonstrated the effectiveness of their therapeutic effects. In this review, the clinical effects of natural compounds extracted from Aconitum sp., focusing on aconitelike alkaloids, are investigated particularly by bioinformatics tools, such as the quantitative structure- activity relationship method, molecular docking, and predicted pharmacokinetic and pharmacodynamic profiles. The experimental and bioinformatics aspects of aconitine's pharmacogenomic profile are discussed. Our review could help shed light on the molecular mechanisms of Aconitum sp. compounds. The effects of several aconite-like alkaloids, such as aconitine, methyllycacintine, or hypaconitine, on specific molecular targets, including voltage-gated sodium channels, CAMK2A and CAMK2G during anesthesia, or BCL2, BCL-XP, and PARP-1 receptors during cancer therapy, are evaluated. According to the reviewed literature, aconite and aconite derivatives have a high affinity for the PARP-1 receptor. The toxicity estimations for aconitine indicate hepatotoxicity and hERG II inhibitor activity; however, this compound is not predicted to be AMES toxic or an hERG I inhibitor. The efficacy of aconitine and its derivatives in treating many illnesses has been proven experimentally. Toxicity occurs as a result of the high ingested dose; however, the usage of this drug in future research is based on the small quantity of an active compound that fulfills a therapeutic role.
Keywords: bioinformatics